The association between Parkinson's disease and anti-epilepsy drug carbamazepine: a case–control study using the UK General Practice Research Database - Skow, Áine (Blackwell Science Inc, 2013)
AIMS: To investigate whether the use of carbamazepine is associated with reduced risk of Parkinson's disease. METHODS: We conducted a population-based, matched case–control study of patients randomly selected from the UK General Research Practice Database. We identified 8549 patients with Parkinson's disease using diagnosis criteria with a positive predictive value of 90%. These patients were compared with 42 160 control subjects matched for age, sex and general practice. RESULTS: Overall, 3.0% of cases (257 of 8549) had at least one recorded prescription for carbamazepine compared with 2.5% (1050 of 42 160) of controls. The crude odds ratio for the association between Parkinson's disease and carbamazepine was 1.22 (95% confidence interval 1.06–1.40), but this reduced to 0.93 (95% confidence interval 0.81–1.08, P = 0.34) after adjusting for annual consultation rate. Further adjustment for body mass index, smoking status, alcohol consumption or use of calcium channel blockers did not affect results. There was no evidence that risk decreased with higher doses or longer duration of carbamazepine use. CONCLUSIONS: There was little to no evidence that use of carbamazepine is associated with reduced risk of Parkinson's disease. Although the study was underpowered, it does indicate that any effect of carbamazepine is likely to be small.